One-pot synthesis of cyanohydrin derivatives from alkyl bromides via incorporation of two one-carbon components by consecutive radical/ionic reactions - Sumino, Shuhei; Fusano, Akira; Okai, Hiroyuki; Fukuyama, Takahide; Ryu, Ilhyong (Beilstein Journal of Organic Chemistry, 2014)
The consecutive radical/ionic reaction consisting of radical formylation of alkyl bromides and nucleophilic addition of a cyanide ion was investigated, which gave moderate to good yields of cyanohydrin derivatives in one-pot.
Keywords: alkyl bromide; carbon monoxide; cyanohydrin; ethyl cyanoformate; multicomponent; radical reaction